Mass-spectrometry analysis of modifications at DNA termini induced by DNA polymerases - Igor P. Smirnov; Natalia A. Kolganova; Vadim A. Vasiliskov; Alexander V. Chudinov; Edward N. Timofeev (Scientific Reports, 2017)
Abstract Non-natural nucleotide substrates are widely used in the enzymatic synthesis of modified DNA. The terminal activity of polymerases in the presence of modified nucleotides is an important, but poorly characterized, aspect of enzymatic DNA synthesis. Here, we studied different types of polymerase activity at sequence ends using extendable and non-extendable synthetic models in the presence of the Cy5-dUTP analog Y. In primer extension reactions with selected exonuclease-deficient polymerases, nucleotide Y appeared to be a preferential substrate for non-templated 3′-tailing, as determined by MALDI mass-spectrometry and gel-electrophoresis. This result was further confirmed by the 3′-tailing of a non-extendable hairpin oligonucleotide model. Additionally, DNA polymerases induce an exchange of the 3′ terminal thymidine for a non-natural nucleotide via pyrophosphorolysis in the presence of inorganic pyrophosphate. In primer extension reactions, the proofreading polymerases Vent, Pfu, and Phusion did not support the synthesis of Y-modified primer strand. Nevertheless, Pfu and Phusion polymerases were shown to initiate terminal nucleotide exchange at the template. Unlike non-proofreading polymerases, these two enzymes recruit 3′–5′ exonuclease functions to cleave the 3′ terminal thymidine in the absence of pyrophosphate.